Russian–Turkish relations before and after the Treaties of Karlowitz - Kijas, Artur (Balcanica Posnaniensia. Acta et studia, 2003)
The article presents the dynamics of Russian-Turkish relations in the period from 1670 to 1711, with particular emphasis on the events before and after the Treaty of Karlowitz (1699). The aim is to show how Russia developed its presence on the European scene with a view to limiting Ottoman political and military influences. Particular attention is paid to Russian expeditions to Crimea and Azov, the policies of Peter I, and the diplomatic activities of Pyotr Tolstoy. The author also presents the context of the conclusion of peace in Istanbul in 1700 and the consequences of the war 1700–1711, which temporarily limited Russian expansion in the Black Sea region. The source material consists of archival materials, including Peter I's correspondence, diplomatic documents, and Russian and Western European literature. According to the author, although the Russian-Turkish peace of 1700 temporarily postponed Russian plans for domination in the south, the diplomatic and military actions carried out during the period in question paved the way for future expansion in the Black Sea region. Tolstoy's mission in Istanbul played a key role in maintaining the delicate balance in relations with the Ottoman Empire.